2015
DOI: 10.4236/ojmip.2015.51002
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Factor-Kappa B and Other Oxidative Stress Biomarkers in Serum of Autistic Children

Abstract: The aim of the present study was to investigate the status of oxidative stress in the serum of children affected with autism spectrum disorder. Twenty autistic children aged 3 to 12 years, were gender and age-matched with 20 typically developing children. Changes in the levels of the redox-sensing transcription factor nuclear factor-kappa B (NF-κB) was measured in serum of autistic children and controls. Other oxidative stress biomarkers such as malondialdehyde, reduced glutathione, total antioxidant capacity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 60 publications
(41 reference statements)
0
7
0
Order By: Relevance
“…This enzyme possesses an esterase and lactonase activities and is involved in xenobiotic metabolism (La Du, 1992) and in protection against oxidative and inflammatory events (Ng et al, 2008). The activity of PON-1 decreases in serum from patients with chronic liver disease (Keskin et al, 2009) and in a number of neurological disorders (Menini and Gugliucci, 2014;Abdel-Salam et al, 2015). We in addition demonstrated that brain butrylcholinesterase (BChE) activity was significantly inhibited by EtOH.…”
Section: Discussionmentioning
confidence: 88%
“…This enzyme possesses an esterase and lactonase activities and is involved in xenobiotic metabolism (La Du, 1992) and in protection against oxidative and inflammatory events (Ng et al, 2008). The activity of PON-1 decreases in serum from patients with chronic liver disease (Keskin et al, 2009) and in a number of neurological disorders (Menini and Gugliucci, 2014;Abdel-Salam et al, 2015). We in addition demonstrated that brain butrylcholinesterase (BChE) activity was significantly inhibited by EtOH.…”
Section: Discussionmentioning
confidence: 88%
“…Furthermore, sialic acid modification of TLR4 can regulate the nuclear factor kappa-B (NF-κB) signaling pathway and lead to altered the protein expression level of cytokines ( 29 , 30 ). Significantly increased serum NF-κB concentration was found in children with ASD ( 31 ). Animal experiments have shown that TLR4 expression is increased in mice with maternal LPS exposure, and their offspring exhibit ASD-like behaviors ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Kishi et al (2016) reported that genetically reducing NF-κB signaling in Mecp2-null mice not only ameliorated cortical callosal projection neurons and dendritic complexity, but also substantially extended their normally shortened lifespan [31]. In studies with human samples, several reports indicate that NF-κB concentrations were elevated in the serum of subjects with ASD and postmortem samples of orbitofrontal cortex tissues [61,62].…”
Section: Discussionmentioning
confidence: 99%